ANALISIS PENANGANAN NASABAH YANG MENINGGAL SEBELUM JATUH TEMPO TERHADAP AKAD MURABAHAH DI KSPPS BMT NU SEJAHTERA KCP MANTINGAN NGAWI - Purvitasari, Yosi (Fakultas Ekonomi Bisnis Islam, 2024)
Murabahah financing is a form of financing based on a sale and purchase agreement that is commonly used in Islamic financial institutions. The Covid-19 pandemic has had a significant impact on the implementation of this agreement, especially when a financing member dies before the payment of obligations. This study aims to analyze the mechanism for handling murabahah financing for members who die before the payment due date at KSPPS BMT NU Sejahtera KCP Mantingan Ngawi, and to review its compliance with DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000 concerning Murabahah. The method used is a descriptive qualitative approach with data collection techniques through interviews and documentation. The results of the study show that in the old provisions, the heirs are obliged to pay off the remaining financing. However, based on the new policy, KSPPS BMT NU Sejahtera provides a solution through submitting a life insurance claim. After the claim process is approved, the obligations of the deceased member are declared paid off without burdening the heirs. This mechanism is in line with sharia principles that allow for special agreements as long as they do not conflict with the provisions of the murabahah agreement. Thus, this handling is considered effective and in accordance with the DSN-MUI fatwa, and provides legal and economic protection for related parties.